(untitled) (Asian Journal of Social Science Studies, 2022)
Effectivités is a unique principle developed in the process of settling territorial disputes by the International Court of Justice. It is gradually developed in judicial practice and plays a very important role in settling territorial disputes. From the perspective of the case of territorial and maritime dispute between Nicaragua and Colombia, which was tried by the International Court of Justice in 2012, and combined with other cases that applied Effectivités, this paper analyzes and discusses the basic theoretical basis and considerations of the application of this principle by the International Court of Justice, and the relationship between this principle and other applicable sources or rules of international law.